Inhomogeneity in barrier height at graphene/Si (GaAs) Schottky junctions. (1st May 2015) - Tomer, D; Rajput, S; Hudy, L J; Li, C H; Li, L
Abstract: Graphene (Gr) interfaced with a semiconductor forms a Schottky junction with rectifying properties, however, fluctuations in the Schottky barrier height are often observed. In this work, Schottky junctions are fabricated by transferring chemical vapor deposited monolayer Gr onto n-type Si and GaAs substrates. Temperature dependence of the barrier height and ideality factor are obtained by current–voltage measurements between 215 and 350 K. An increase in the zero bias barrier height and decrease in the ideality factor are observed with increasing temperature for both junctions. Such behavior is attributed to barrier inhomogeneities that arise from interfacial disorders as revealed by scanning tunneling microscopy/spectroscopy. Assuming a Gaussian distribution of the barrier heights, mean values of 1.14 ± 0.14 eV and 0.76 ± 0.10 eV are found for Gr/Si and Gr/GaAs junctions, respectively. These findings resolve the origin of barrier height inhomogeneities in these Schottky junctions.